2019
DOI: 10.3892/etm.2019.8173
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mitochondrial biogenesis is associated with the ameliorative action of creatine supplementation in rat soleus and cardiac muscles

Abstract: The current study focused on the effect of creatine supplementation with/without exercise on the expression of genes controlling mitochondrial biogenesis in skeletal and cardiac muscles, as well as its safety profile on the liver and kidney. A total of 40 male Wister rats were included in the present study. Two unexercised groups: The control sedentary group and the sedentary creatine-treated group (n=10) were treated daily with oral creatine (0.5 g/kg per day). Two exercised groups performed swimming exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…A specific primer pair for mtDNA and a primer pair for the nuclear PGC-1α gene (Table 1 ) were used. PCR reactions were carried out using SYBR Green PCR Master Mix (Qiagen, Germany), 0.5 μM of each primer pair, and 50 ng genomic DNA under the following conditions: 95˚C for 10 min followed by 40 cycles of 95 °C for 15 s, 60 °C for 30 s and 72 °C for 30 s (Gowayed et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…A specific primer pair for mtDNA and a primer pair for the nuclear PGC-1α gene (Table 1 ) were used. PCR reactions were carried out using SYBR Green PCR Master Mix (Qiagen, Germany), 0.5 μM of each primer pair, and 50 ng genomic DNA under the following conditions: 95˚C for 10 min followed by 40 cycles of 95 °C for 15 s, 60 °C for 30 s and 72 °C for 30 s (Gowayed et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…A specific primer pair for mtDNA (forward: 5’-ACACCAAAAGGACGAACCTG-3’; reverse: 5’-ATGGGGAAGAAGCCCTAGAA-3’) and a primer pair for the nuclear PGC-1α gene (forward: 5’-ATGAATGCAGCGGTCTTAGC-3’; reverse: 5’-AACAATGGCAGGGTTTGTTC-3’) were used. PCR reactions were carried out using Rotor Gene SYBR Green PCR Kit (Qiagen ® , Germantown, MA, USA), 0.5 µM forward and reverse primer, and 50 ng of extracted DNA under the following conditions: 95 °C for 10 min followed by 40 cycles of 95 °C for 15 s, 60 °C for 30 s, and 72 °C for 30 s [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…21 Lastly, it has been previously reported that exercise may lead to an increment in mitochondrial biogenesis because the free radicals generated during exercise become signals for PGC-1α to promote mitochondrial biogenesis. 22 In summary, PGC-1α and PPARs could promote mitochondrial biogenesis, resulting in increased mtDNA.…”
Section: Mitochondria-related Processesmentioning
confidence: 99%
“…Besides, it has been reviewed that PPAR-α and PPAR-γ could also get involved, possibly by activating those transcription factors to promote mitochondria biogenesis . Lastly, it has been previously reported that exercise may lead to an increment in mitochondrial biogenesis because the free radicals generated during exercise become signals for PGC-1α to promote mitochondrial biogenesis . In summary, PGC-1α and PPARs could promote mitochondrial biogenesis, resulting in increased mtDNA.…”
Section: Mitochondria-related Processesmentioning
confidence: 99%